The Diagnostic Dilemma of a Granulomatous Gingival Enlargement. Issue 1 (1st February 2015) - Naik, Ryschia R.; Bhat, Subraya G.; Carnelio, Sunitha; Natarajan, Jayalakshmi; Bhat, Mahalinga
Abstract : Introduction: The oral cavity is considered an easily accessible window to the body. The mouth is frequently involved in conditions that affect multiple organs. In many instances, oral involvement precedes the appearance of many other symptoms or lesions. A complete examination of the oral cavity provides a gateway for an accurate diagnosis and precise management of many systemic conditions. Gingival enlargement is one of the varied manifestations of many systemic diseases. Here, a case report of a gingival enlargement is presented that provided information for the diagnosis of post‐primary pulmonary tuberculosis. Case Presentation: A 62‐year‐old female presented with a persistent gingival enlargement of 6‐month duration, which was non‐responsive to periodontal therapy. A complete general examination with the help of additional diagnostic aids provided the diagnosis of post‐primary pulmonary tuberculosis. Conclusion: Clinicians should be aware of the unusual forms of common diseases, which will aid in early diagnosis and proper patient management.